Study of the Effects of 3 h of Continuous Cardiopulmonary Resuscitation at 27°C on Global Oxygen Transport and Organ Blood Flow - Nilsen, Jan Harald; Valkov, Sergei; Mohyuddin, Rizwan; Schanche, Torstein; Kondratiev, Timofei V.; Naesheim, Torvind; Sieck, Gary C.; Tveita, Torkjel (Frontiers in Physiology, 2020)
Aims Complete restitution of neurologic function after 6 h of pre-hospital resuscitation and in-hospital rewarming has been reported in accidental hypothermia patients with cardiac arrest (CA). However, the level of restitution of circulatory function during long-lasting hypothermic cardiopulmonary resuscitation (CPR) remains largely unknown. We compared the effects of CPR in replacing spontaneous circulation during 3 h at 27°C vs. 45 min at normothermia by determining hemodynamics, global oxygen transport (DO2), oxygen uptake (VO2), and organ blood flow. Methods Anesthetized pigs (n = 7) were immersion cooled to CA at 27°C. Predetermined variables were compared: (1) Before cooling, during cooling to 27°C with spontaneous circulation, after CA and subsequent continuous CPR (n = 7), vs. (2) before CA and during 45 min CPR in normothermic pigs (n = 4). Results When compared to corresponding values during spontaneous circulation at 38°C: (1) After 15 min of CPR at 27°C, cardiac output (CO) was reduced by 74%, mean arterial pressure (MAP) by 63%, DO2 by 47%, but organ blood flow was unaltered. Continuous CPR for 3 h maintained these variables largely unaltered except for significant reduction in blood flow to the heart and brain after 3 h, to the kidneys after 1 h, to the liver after 2 h, and to the stomach and small intestine after 3 h. (2) After normothermic CPR for 15 min, CO was reduced by 71%, MAP by 54%, and DO2 by 63%. After 45 min, hemodynamic function had deteriorated significantly, organ blood flow was undetectable, serum lactate increased by a factor of 12, and mixed venous O2 content was reduced to 18%. Conclusion The level to which CPR can replace CO and MAP during spontaneous circulation at normothermia was not affected by reduction in core temperature in our setting. Compared to spontaneous circulation at normothermia, 3 h of continuous resuscitation at 27°C provided limited but sufficient O2 delivery to maintain aerobic metabolism. This fundamental new knowledge is important in that it encourages early and continuous CPR in accidental hypothermia victims during evacuation and transport.